Characterizing Lyme Disease Surveillance in an Endemic State. (29th July 2016) - Rutz, H. J.; Wee, SB.; Feldman, K. A.
Summary: Lyme disease (LD) is the most common vector‐borne disease in Maryland and the United States. Surveillance for LD is valuable for understanding the burden of the disease, particularly to assess whether the disease is spreading and to appreciate who is affected. However, not all cases of LD in Maryland are reported, and surveillance practices vary across each of Maryland's 24 local health departments (LHDs). To better understand this variability and to systematically characterize the surveillance process, we surveyed Maryland's LHDs regarding LD surveillance. The Maryland Local Health Department Lyme Disease Surveillance Survey has been administered annually since 2011. Questions asked each year included whether all LD reports are investigated or only a subset, and how many reports are not entered into the surveillance database. Since 2011, Maryland has lost surveillance personnel for LD. Each year from 2009 to 2012, a median 3598 (range 2462 to 5722) reports were not entered into the surveillance database and hence not investigated. These reports represent 43–55% of all reports received for the year. Over time, more LHDs chose to streamline their LD investigation approach by investigating only those reports that met the criteria for laboratory evidence of infection: in 2008, 5 (21%) LHDs investigated only a subset of LD reports; by 2013, this increased to 15 (63%). There is wide variability across LHDs in how LD investigations are conducted. Maryland LHDs have experienced a loss of LD surveillance personnel with a concomitant increase in the number of LHDs adopting a streamlined approach to investigating cases. These findings underscore the tremendous burden of LD on the public health agencies and highlight the need for alternative approaches that can both reduce burden and preserve surveillance data quality.